THE EFFECTIVENESS OF PROGRESSIVE MUSCLE RELAXATION ON BLOOD SUGAR LEVELS OF TYPE 2 DIABETES MELLITUS PATIENTS - Difran Nobel Bistara; Susanti Susanti (Jurnal Keperawatan Respati Yogyakarta, 2022)
During the pandemic diabetes itself becomes the most dangerous comorbid because diabetes increases the risk of more severe complications when infected with the Corona virus. With restrictions on activities outside the home during the pandemic, inevitably many people have to do all activities at home, but precisely because of this, many people are neglectful of lifestyle management which ends up running a sententary life. Thus, people with diabetes mellitus do not carry out one of the pillars to stabilize blood sugar levels, namely physical activity. In addition, many diabetics do not know that controlling blood sugar levels can be done non-pharmacologically, one example is relaxation techniques. Most people with Diabetes Mellitus never apply this management because they are considered to have no function. The purpose of this study was to determine the effectiveness of progressive muscle relaxation on blood sugar levels in patients with type 2 diabetes mellitus. The design of this study was quasi-experimental with the type of pretest and posttest intervention. The research population was 36 people and the sample was taken using simple random sampling, each with 18 people. The research instrument used an observation sheet and a glucometer to measure blood sugar levels. Data analysis using the Wilcoxon sign rank test with the result <0.05. The results showed that the results of blood sugar levels before and after Progressive OOT relaxation in the treatment group had a P value = .016, P value <0.05, the hypothesis was accepted that progressive muscle relaxation was effective in reducing blood sugar levels in patients with type 2 diabetes mellitus. 2. Future studies are expected to compare other complementary therapies to stabilize blood sugar levels in patients with type 2 diabetes mellitus.